2020
DOI: 10.1155/2020/6325378
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Protects against Paraquat-Induced Acute Liver Injury in Rats by Regulating Oxidative Stress, Mitochondrial Function, and Inflammation

Abstract: In addition to the lung, the liver is considered another major target for paraquat (PQ) poisoning. Hydrogen sulfide (H2S) has been demonstrated to be effective in the inhibition of oxidative stress and inflammation. The aim of this study was to investigate the protective effect of exogenous H2S against PQ-induced acute liver injury. The acute liver injury model was established by a single intraperitoneal injection of PQ, evidenced by histological alteration and elevated serum aminotransferase levels. Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 83 publications
5
33
0
1
Order By: Relevance
“…Wu et al (2016) observed that S-propargyl-cysteine, an endogenous inductor of H 2 S synthesis, activates Nrf-2 signaling in adjuvant-induced arthritis rats and inhibits inflammatory response, ameliorating the severity of the arthritis model [ 46 ]. Hence, a growing number of evidences suggest that the Nrf-2 activation induced by H 2 S is also responsible for its anti-inflammatory effects [ 46 , 63 , 64 ]. In our study, we observed for the first time that the administration of a slow-releasing H 2 S donor in the joint induces the expression of Nrf-2 in the cartilage and that this event could contribute to the attenuation of the expression of pro-inflammatory markers detected in our model and subsequently to its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (2016) observed that S-propargyl-cysteine, an endogenous inductor of H 2 S synthesis, activates Nrf-2 signaling in adjuvant-induced arthritis rats and inhibits inflammatory response, ameliorating the severity of the arthritis model [ 46 ]. Hence, a growing number of evidences suggest that the Nrf-2 activation induced by H 2 S is also responsible for its anti-inflammatory effects [ 46 , 63 , 64 ]. In our study, we observed for the first time that the administration of a slow-releasing H 2 S donor in the joint induces the expression of Nrf-2 in the cartilage and that this event could contribute to the attenuation of the expression of pro-inflammatory markers detected in our model and subsequently to its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The reports display that 5–15 ml of 20% concentration of paraquat can result in moderate or severe poisoning ( Wesseling et al, 2001 ; Baltazar et al, 2013 ). Several studies have shown that exposing to paraquat can induce liver injury by decreasing antioxidant capacity and stimulation of inflammation ( Gao et al, 2020a ; Liu et al, 2020c ). Although studies have put much emphasis on the involvement of oxidative stress and inflammation in paraquat-mediated toxicity, the role of TGF-β signaling pathway is uncertain in liver toxicity.…”
Section: Curcumin and Transforming Growth Factor-beta In Different DImentioning
confidence: 99%
“…Nonenzymatic scavengers mainly include thioredoxin (Trx), glutathione (GSH), as well as low-molecular-weight antioxidants like cytochrome c and coenzyme Q. The process that GSH is oxidized to GSH disulfide (GSSG) through the interaction with GSH S-transferase directly or via a reaction catalyzed by GSH-Px could alleviate oxidative damage through decreasing disulfide bonds of cytoplasmic proteins to cysteines [ 54 ]. Excessive ROS can induce an oxidized Trx form, which is subsequently converted to a functionally reductive form by thioredoxin reductase (TrxR) to maintain redox homeostasis in cells [ 55 ] ( Figure 1 ).…”
Section: Cellular Detoxification From Ros Of Pcamentioning
confidence: 99%